Energizing Green Cities in Southeast Asia: Applying Sustainable Urban Energy and Emissions Planning - Ostojic, DejanR. (World Bank, 2015)
Cities currently account for about two-thirds of the world’s annual energy consumption and about 70 percent of greenhouse gas (GHG) emissions. In the coming decades, urbanization and income growth in developing countries are expected to push cities? energy consumption and GHG emissions shares even higher, particularly where the majority of people remain underserved by basic infrastructure services and where city authorities are under resourced to shift current trajectories. These challenges are faced by many cities and millions of people in the East Asia and Pacific (EAP) Region, which is experiencing unprecedented rates of urbanization, as the region’s urban population grows almost twice as fast as the world’s urban population.